HUBUNGAN ANTARA PEMAHAMAN NOTASI ANGKA DENGAN KEMAMPUAN MENYANYIKAN SOLFEGGIO/ SOLMISASI PADA PEMBELAJARAN SENI MUSIK - Yohana Lopo; Paskalis R Langgu; Gregorius V Ukat (Program Studi Pendidikan Musik, 2026)
Music education in schools requires a balance between theoretical knowledge and practical skills. Understanding number notation is an important foundation for reading and singing melodies, including in solfeggio exercises. This study aims to analyze the relationship between understanding number notation and the ability to sing solfeggio in grade XC students at St. Arnoldus Janssen Kupang High School. The method used is quantitative research with a correlational design. The sample consisted of 37 students, obtained through total sampling technique. Data were collected using a musical notation understanding questionnaire and a solfeggio singing ability test, then analyzed using the Shapiro–Wilk normality test and Pearson Product Moment correlation test. The results showed that both variables were normally distributed and there was a positive and significant relationship between understanding musical notation and solfeggio singing ability, as indicated by a value of r = 0.512 with Sig. = 0.002. These findings indicate that the higher the students' level of understanding of musical notation, the better their ability to sing solfeggio musically. This study confirms that strengthening music theory, especially musical notation, needs to be integrated with vocal exercises to support the development of students' singing skills.